Medium Chain Fatty Acids Are Selective Peroxisome Proliferator Activated Receptor (PPAR) gamma Activators and Pan-PPAR Partial Agonists - Liberato, Marcelo Vizona; Nascimento, Alessandro S.; Ayers, Steven D.; Lin, Jean Z.; Cvoro, Aleksandra; Silveira, Rodrigo L.; Martinez, Leandro; Souza, Paulo C. T.; Saidemberg, Daniel [UNESP]; Deng, Tuo; Amato, Angela Angelica; Togashi, Marie; et al. (Public Library Science, 2012)
Thiazolidinediones (TZDs) act through peroxisome proliferator activated receptor (PPAR) gamma to increase insulin sensitivity in type 2 diabetes (T2DM), but deleterious effects of these ligands mean that selective modulators with improved clinical profiles are needed. We obtained a crystal structure of PPAR gamma ligand binding domain (LBD) and found that the ligand binding pocket (LBP) is occupied by bacterial medium chain fatty acids (MCFAs). We verified that MCFAs (C8-C10) bind the PPAR gamma LBD in vitro and showed that they are low-potency partial agonists that display assay-specific actions relative to TZDs; they act as very weak partial agonists in transfections with PPAR gamma LBD, stronger partial agonists with full length PPAR gamma and exhibit full blockade of PPAR gamma phosphorylation by cyclin-dependent kinase 5 (cdk5), linked to reversal of adipose tissue insulin resistance. MCFAs that bind PPAR gamma also antagonize TZD-dependent adipogenesis in vitro. X-ray structure B-factor analysis and molecular dynamics (MD) simulations suggest that MCFAs weakly stabilize C-terminal activation helix (H) 12 relative to TZDs and this effect is highly dependent on chain length. By contrast, MCFAs preferentially stabilize the H2-H3/beta-sheet region and the helix (H) 11-H12 loop relative to TZDs and we propose that MCFA assay-specific actions are linked to their unique binding mode and suggest that it may be possible to identify selective PPAR gamma modulators with useful clinical profiles among natural products.